Polycyclic Aromatic Hydrocarbons (PAHs) and Their Influence to Some Aquatic Species - Baali, Ayoub (2020)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants generated primarily during the incomplete combustion of organic materials (e.g., coal, oil, petrol, and wood). Many PAHs have toxic, mutagenic, and/or carcinogenic functions. PAHs are highly lipid soluble which lead to a fast absorption by the gastrointestinal tract of marine mammals. They are immediately distributed in a vast variety of tissues with a notable tendency for localization in body fat. Metabolism of PAHs is obtained via the cytochrome P450-mediated mixed function oxidase system with oxidation or hydroxylation as the first step. PAHs are environmental contaminants that pose significant risk to health of fish. The effect of PAHs on fish is a topic of rising attention in a lot of countries. Different studies using the bile metabolites separated by high-performance liquid chromatography with fluorescence detection were presented. The aim is to compare the levels of PAH metabolites in fish from different areas and fish species. The major metabolite present in all fish was 1-hydroxypyrene. The data confirm the importance of 1-hydroxypyrene as the key PAH metabolite in fish bile and suggest that the European eel is an ideal species for monitoring PAHs.